2018
DOI: 10.1055/s-0038-1641598
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Groin Surgery during Childhood on the Incidence of Inguinal Hernia Repair and Its Postoperative Complications in Adult Life

Abstract: Individuals undergoing surgery in the groin during childhood are at increased risk for acquired inguinal hernia surgery later in life. Inguinal surgery during childhood did not affect the outcome of hernia repair in adult age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We do not have any information about previous IH as a child; a previous study identified a slightly increased risk of IH formation later in life if a male has undergone IH repair in childhood (Sokratous et al, 2019). This increase is so small that we believe that the large cohort will cover for this.…”
Section: Discussionmentioning
confidence: 99%
“…We do not have any information about previous IH as a child; a previous study identified a slightly increased risk of IH formation later in life if a male has undergone IH repair in childhood (Sokratous et al, 2019). This increase is so small that we believe that the large cohort will cover for this.…”
Section: Discussionmentioning
confidence: 99%
“…However, nationwide data have been scarcely presented for paediatric inguinal hernias and were largely restricted to Denmark [ 2 ], Taiwan [ 3 ], and England [ 4 ] based on their large health insurance-based registries. The Swedish registry data has so far only been used to investigate specific narrow research questions in adolescents [ 5 ], as has a large insurance database in Japan [ 6 ]. Contrary to this situation in paediatric inguinal hernia repair, research in adults may not only rely on large-scale registries from different countries [ 7 ], but also on routine administrative data [ 8 ] and even the combination of both [ 9 ].…”
Section: Introductionmentioning
confidence: 99%